Do characteristics of CEO and chairman influence government-linked companies performance? - Amran, Noor Afza; Md Yusof, Mohd Atef; Ishak, Rokiah; Aripin, Norhani (2013)
Chairman is the leader of the board, responsible to ensure that board is effective, communicate with the shareholders and a good relationship between board.While the Chief Executive Officer (CEO) plays a major role in managing and ensuring the business operations.This study examines the characteristics of CEO and Chairman of Government Linked Companies (GLCs) in Malaysia with firm performance using a sample of 80 companies for the period 2005-2009.This study finds that there are positive relationship among chairman's age, ethnicity, firm size and firm age, when regressed on Return on Assets (ROA).In terms of CEO characteristics, there are negative relationship for professional qualification.CEO age, firm age with ROA.In sum, it can be concluded that factors such as age, ethnicity, professional qualification, firm size and firm age do influence firm performance.